A begonia for Miss Applebaum - Zindel, Paul (Harper & Row, 1989)
Discovering that their beloved former teacher Miss Applebaum is terminally ill, fifteen-year-old Henry and his friend Zelda accompany her on her excursions to the colorful parts of New York City and join her in confronting death with quiet courage.